Ultrafiltração aplicada à remoção do agrotóxico glifosato e do seu principal metabólito (AMPA) em águas de abastecimento: avaliação em escala de bancada - Reis, Dariene Patrícia dos (2015)
The herbicide glyphosate is currently one of the most used agricultural products in the world. Farmers from Espirito Santo (ES), Brazil, uses this agrochemical for cultivation of banana, coffee and chemical weeding. The aminomethylphosphonic acid (AMPA) is produced by glyphosate degradation, and may be considered a more aggressive compound to the environment than glyphosate. With the advancement of membrane technology, and the possibility that this type of treatment can be replace conventional water treatment, it is necessary to study the effectiveness of this procedure for different micropollutants that can be contamined rivers in Brazil. Thus the present study evaluated the removal of the herbicide glyphosate and its major metabolite AMPA through the ultrafiltration process using water collected in Water Treatment Plant Carapina, from Santa Maria da Vitória river. The feed’s wather and the permeate were evaluated for the parameters: turbidity, pH, electrical conductivity, real and apparent color, absorbance at 254 nm and total organic carbon (TOC). In the laboratory there fortification of water samples with solutions of glyphosate and AMPA to obtain concentrations of 630, 800 and 1250 μ.L-1 in the feed. Besides the effect of concentration was also checked for the effect of pH and adsorption to determine the form of rejection UF membrane. There was a slight tendency of increase in removal basic (pH = 10) also observed an increase in the removal from the increased concentration in the permeate. The mass balance indicated that occurs adsorption of glyphosate and AMPA molecules (adsorbed average mass of 1.3 µg.cm-2 ), but the rejection occurs in most of the effects of interaction between charges (membrane-solute) and size exclusion. There was an effective removal of turbidity and apparent color. This was necessary to produce permeate with values lower than the permissible maximum limit for these parameters required by legislation. The results however have shown some effectiveness in the removal of conductivity and UV 254nm. The rejection of microcontaminants assessment also proved ineffective presenting efficiency below 50% for all tests. The use of UF is able to produce permeate whith value below than the limits of 2914/2011 when glyphosate and AMPA concentrations in the permeate have slightly higher values than the LMP 500 μg.L-1